Value of [11C]-Methionine PET/CT in Preoperative Localization of Parathyroid Adenomas - Saerens, Julie; Velkeniers, Brigitte; Keyaerts, Marleen; Raeymaeckers, Steven; Vanhoeij, Marian; Blotwijk, Susanne; Bravenboer, Bert (Hormone and Metabolic Research, 2021)
There are multiple imaging modalities in primary hyperparathyroidism. Ultrasound examination and subtraction scintigraphy are usually the first-line imaging techniques. When these results are negative or inconsistent, additional [11C]-methionine PET/CT (MET-PET/CT) or 4-dimensional computed tomography can be performed. ​This study aims to evaluate MET-PET/CT in comparison with other imaging techniques in primary hyperparathyroidism. This is a retrospective cohort study. Eighty-four patients with primary hyperparathyroidism, who underwent parathyroid surgery, were included. ​Imaging results have been correlated to the perioperative drop in parathyroid hormone level and to the pathological analysis. ​Descriptive statistics are used, supplemented with 95% Clopper–Pearson confidence intervals for sensitivity and specificity and a sub-analysis with the McNemar test on paired data only. The per-lesion sensitivity of MET-PET/CT seems higher than that of [99mTc]-sestamibi or [99mTc]-tetrofosmin and [99mTc]-pertechnetate subtraction scintigraphy. The McNemar test, on paired data only, shows significantly higher sensitivity of MET-PET/CT compared to ultrasound (p=0.039) and significantly higher specificity of ultrasound compared to subtraction scintigraphy (p=0.035).​ MET-PET/CT after inconclusive or negative ultrasound and/or subtraction scintigraphy has an additional value in 70% of the cases.​ Preoperative parathyroid hormone levels were higher in patients in whom MET-PET/CT correctly predicted the pathological parathyroid glands, compared to those where MET-PET/CT missed at least one adenoma. The same trend was seen for 4-dimensional computed tomography. In conclusion, MET-PET/CT seems a valuable imaging modality in primary hyperparathyroidism, at least as second line imaging approach, with a higher per-lesion sensitivity than ultrasound in such setting. Especially when ultrasound and/or subtraction scintigraphy are inconclusive or negative, MET-PET/CT directs the surgeon to the correct localization of the parathyroid adenoma.
Keywords: primary hyperparathyroidism; subtraction scintigraphy; ultrasound; 4-dimensional computed tomography